The Mutual Relation of Platelet Activation and Innate Immunity - Eisinger, Felix; Langer, Harald F. (Hämostaseologie, 2018)
Platelets are known to be central regulators of haemostasis, inflammation and immune response. Formed by megakaryocytes in the bone marrow and the lungs, platelets express a broad range of adhesion receptors and release cytokines and platelet microparticles which enable them to interact with both immune cells and pathogens. In bacterial and viral infections, thrombophilia and thrombocytopenia are commonly seen symptoms, indicating the close relationship between haemostasis and immune defence. Indeed, platelets contribute both directly and via immune mediation to pathogen clearance. In sterile inflammation, a pathogen-free process which is often triggered by cell necrosis and autoimmune reactions, platelets are also of central importance. Recently, platelet inflammasome has been extensively studied in this context. Both sterile inflammation and infection are affected by the interactions of platelets and innate immunity, notably the complement system. Although the general elements of this interplay have been known for long, more and more insights into disease-specific mechanisms could be gained recently. This review gives an outline of the current findings in the field of platelet–immune cell interactions and points out possible implications for clinical therapy.
Keywords: platelets; innate immunity; inflammation; infection; cytokines; inflammasome; leukocytes; complement system